The annotated statutes of Malaysia: mutual assistance in criminal matters act 2002 (Act 621) - Islam, Md. Zahidul, (LexisNexis, 2019)
an annotated statute on criminal matters Act 2001 (Act 621) the issue states the law as at 15 May 2019